Aspects Of Job Stress, Work Motivation And Work Discipline On Employee Job Performance - Said, Muhammad; Dwinanda, Giri; Ikram, Ahmad (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to examine the aspects of work stress, work motivation and work discipline that influence employee work performance. The population in this study was all employees at the director's office of PT Perkebunan Nusantara XIV, Makassar City, totaling 134 people. Sampling in this study used a purposive sampling technique so that the total sample used was 57 people. The data collection method in this research uses a questionnaire. A questionnaire is a data collection method that is carried out by providing statements to respondents using a questionnaire guide. The questionnaire was processed and analyzed using multiple linear regression analysis methods. The research results found that work stress had a negative and significant effect on work performance, while work motivation and work discipline each had a positive and significant effect on work performance.